2008
DOI: 10.1002/bit.21887
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient gradients in engineered cartilage: Metabolic kinetics measurement and mass transfer modeling

Abstract: Since tissue-engineered cartilage is avascular, both nutrient supply and metabolic waste removal rely on diffusion. As a result, gradients of nutrients and wastes exist through the construct. Previous models usually calculate gradients of oxygen, glucose, and lactic acid separately, without taking into account the complex interdependence between concentrations of these substrates and rates of metabolism. In this study, these interactions were experimentally examined and incorporated into diffusion models. One-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 52 publications
5
64
0
Order By: Relevance
“…This choice was motivated by the desire to maintain the glucose concentration at the standard 25 mM of high-glucose DMEM and the concern that large changes in concentration might produce confounding effects due to alterations in osmolality and pH. 10,47 Another potential concern is that large numbers of channels may compromise the construct mechanical integrity, possibly leading to stress concentrations and cracking under loading. No cracking was observed during mechanical testing on day 56, although the possibility that such damage may occur at physiological load magnitudes should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice was motivated by the desire to maintain the glucose concentration at the standard 25 mM of high-glucose DMEM and the concern that large changes in concentration might produce confounding effects due to alterations in osmolality and pH. 10,47 Another potential concern is that large numbers of channels may compromise the construct mechanical integrity, possibly leading to stress concentrations and cracking under loading. No cracking was observed during mechanical testing on day 56, although the possibility that such damage may occur at physiological load magnitudes should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…The computational model employed herein builds from earlier efforts to model engineered cartilage nutrient consumption 25,[47][48][49][50][51] and serves as a critical step to develop systemspecific models for assessing the culture of the characterized CTE systems. Models may similarly guide future studies by identifying the most promising experimental culture conditions for a given construct geometry and cell density, eliminating less promising ones, and reducing the need for labor-and cost-intensive experimental parametric studies.…”
Section: Discussionmentioning
confidence: 99%
“…These models, along with cell growth, also account for the consumption of nutrients (mainly oxygen) essential for the cells to grow and proliferate. Factors influencing the oxygen concentration gradient in articular cartilage (from cartilage to bone interface) have been determined experimentally and modelled mathematically by Urban and co-workers (Zhou et al (2004); Zhou et al (2007)). Since articular cartilage is avascular, both nutrient supply and waste removal rely on diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate, the product of glycolysis, is converted in acetil coenzyme A, which is the main supplier of carbon in Krebs cycle. A glucose gradient from the synovial fluid toward the deep zone of cartilage is also present as shown by Zhou et al [68]. Being glucose not only the most important source for energy production, but also a key component in GAG synthesis, it has been shown that across cartilage from the synovial side to the subchondral bone, a glucose gradient exists [69] (Fig.…”
Section: Nutrients/o2 Gradientmentioning
confidence: 87%
“…Nutrient transport is also sometimes thought to be assisted by movement of fluid in and out of cartilage in response to cyclic loading of the tissue [67]. Therefore, gradients of nutrients and metabolic byproducts exist through cartilage due to the balance between transport and rates of cellular metabolism [68]. This process is aided by the presence of proteoglycans that have the ability of retaining water, which flows in with the nutrients during loading relaxation and flows out with the metabolites during compression.…”
Section: Nutrients/o2 Gradientmentioning
confidence: 99%